INDUCTION OF EXTRACELLULAR ENZYME PRODUCTION - Tadjieva Khosiyat Sultanovna; Kosimova Hilola Tokhtapulatovna (Web of Journals Publishing, 2025)
Polycyclic aromatic hydrocarbons (PAHs) are a large class of organic compounds consisting of two or more fused benzene rings. Interest in the mechanisms of biodegradation and the fate of PAHs in the environment is due to their ubiquity, resistance to degradation, accumulation in soil and sediment, and toxic, mutagenic, and carcinogenic properties. Some PAHs are classified as priority pollutants by the U.S. and several other national environmental agencies. PAHs are hydrophobic compounds; their stability within ecosystems is a consequence of their low solubility in water. The discharge and accidental release of PAHs into the environment poses a serious problem, especially when the biodegradative activity of natural microflora is insufficient to remove or neutralize pollutants. Currently, active research is underway to improve technologies for the bioremediation of soils and water contaminated with PAHs. The use of microorganisms represents a highly effective and relatively inexpensive technology for the detoxification of these hazardous pollutants, which can replace traditional methods. The development and effective use of bioremediation requires a comprehensive study of degrader organisms, metabolic pathways for PAH degradation, the enzyme systems that catalyze them, and the environmental conditions necessary to optimize the destruction of these compounds. Currently, the ability to metabolize PAHs has been identified in a number of bacteria, algae, cyanobacteria, and fungi. PAH-degrading fungi can be divided into two groups: non-ligninolytic and ligninolytic. The most active are fungi that naturally destroy the lignin component of wood (ligninolytic). These include mainly wood-dwelling (white rot fungi) and soil-dwelling litter-decomposing saprotrophs basidiomycetes and some species of ascomycetes. The enzymatic system of these fungi, which catalyzes lignin degradation, is extracellular, nonspecific, and oxidative, which allows them, in addition to the natural substrate, to metabolize a wide range of pollutants and their mixtures, giving them a significant advantage over bacteria and non-ligninolytic fungi. The main ligninolytic enzymes are lignin peroxidase, Mn-peroxidase, hybrid peroxidase (in the English version, versatile peroxidase) and laccase. Repression of enzyme synthesis does not occur when concentrations of substances are reduced to a level that is ineffective for their induction, and therefore they can degrade even low concentrations of pollutants.